Spatial relationships between macrophyte assemblages, water and sediment features in deep lakes - Dalla Vecchia, Alice; Bolpagni, Rossano; Laini, Alex; Nizzoli, Daniele; Bresciani, Mariano; Azzella, Mattia Martin; Wilkes, Martin (Frontiers in Environmental Science, 2025)
Despite the global ecological and societal importance of deep lakes and their associated biota and ecosystem services, the relationships between water and sediment features and the spatial patterns of macrophyte assemblages remain poorly understood in these ecosystems, especially below 4–5 m depth. We aimed to fill this gap by providing new evidence of macrophyte community assembly rules over a wide range of colonized depths (up to 20 m). The macrophyte communities of five deep volcanic lakes in Central Italy, covering a wide range of dimensions (from 1.7 to 114.5 km2), maximum depths (from 33 to 165 m), and trophic status [12.4–41.3 μg of total phosphorus (TP) L-1], were explored. We applied linear mixed effect models and multivariate Multiscale Codependence Analysis (mMCA) to investigate macrophyte depth patterns and environmental drivers at nested spatial scales ranging from micro (at the scale of single vegetation belt) to large (whole lake study site) scales. A weak or absent macrophyte spatial structure was reported for the most impacted lakes (Vico and Nemi lakes), as well as for the most pristine lakes (Bracciano and Bolsena lakes). A well-defined structure was observed exclusively in Martignano Lake, an intermediate site both in terms of trophic status (17.1 μg TP L-1) and area (2.02 km2). Overall, distinctive macrophyte patterns were found at the largest lake scale, reflecting a clear distinction between shallow (up to 3 m) and deep vegetated bands (>3 m), dominated by vascular plants and large charophytes, respectively. Conversely, no strong spatial structure was detected at the microscale (i.e., with metric resolution, comparing the different study plots with each other). The low species diversity and the constant presence of only one dominant species per vegetated band can explain this result. Beyond light availability, sediment features (TP and organic matter content) emerged as significant in determining the arrangement of macrophytes in relation to depth, offering a more informed view of macrophyte spatial processes and their functional implications in deep lakes.